Dataset Hippocampal proteomics in a mice model of early life adversity in combination with a second acute stress in adulthood. - Muñoz-Martín, José; Pérez-Martín, Margarita; Pedraza-Benítez, María del Carmen (Universidad de Málaga, 2026)
Proteomic analysis was performed on left hippocampal tissue from C57BL/6J mice subjected to maternal separation during infancy (MS), acute restriction stress in adulthood (RS), or combined MS+RS, compared to controls (CTRL). N=5-6 per group, males and females separately. Hippocampi were collected 24h post RS stress (P62-P65), homogenized in RIPA buffer, quantified by BCA, and digested via gel-assisted proteolysis with trypsin. Samples underwent UHPLC-HRMS on a Q-Exactive HF-X , acquiring MS/MS spectra (SCAI-Universidad de Málaga). Raw data were searched in Proteome Discoverer 2.5 against Mus musculus UniProt (2025-02), yielding 2,895 high-confidence proteins (FDR<1%, ≥2 peptides, master proteins). Label-free quantification used precursor intensities, normalized by total peptide amount; ANOVA identified upregulated (p<0.05, log2 FC≥1) and downregulated proteins (p<0.05, log2FC ≤-1) in the following comparisons: RS vs CTRL, MS vs CTRL, MS+RS vs CTRL, RS vs MS+RS, MS vs MS+RS (males and females, separately). Raw proteomic data as well as volcano plots are distributed in RIUMA (Universidad de Málaga).
Hippocampal proteomics in ELA model: Maternal separation + Restriction Stress
The raw dataset as well as the refined comparisons among experimental conditions are distributed in one EXCEL file (hippocampal_proteomics_results_MSJUL22.xlsx). Volcano plots for every comparison can also be found distributed in the pdf file (volcano_plots_hippocampal_proteomics_MSJUL22.pdf).
Keywords: Estrés (Fisiología); Hipocampo (Cerebro); Proteómica; Psicopatología; Trauma psíquico; Early Life Adversity; Hippocampus; Maternal separation; Restriction stress; Proteomics; Orbitrap; Brain